(untitled) (Fiep Bulletin - online, 2011)
This article is integrant part of the dissertation of Master Degree in Education defended by the author, that report the history of the Physical Education for boys in the Santo Agostinho School in Belo Horizonte, in the period comprehended between 1934 to 1974. In this study are argued the characteristics of "Magazine Santo Agostinho" and her specificities, and the Magazine wealth iconographic gave support for a larger intended historical approach. They were found 11 numbers of the Magazine Santo Agostinho, published in 18 years of School, having as main goal of the publication narrow the relations with the teachers, students and family. The published images presented students’ bodies and teachers in different times, in performance several moments in the educational process, representing the subjects there produced. Also EF and the sport were revealed through small goods and records iconographics, presenting the school as own space for the pedagogy actions development of the social, rational and national purification.